Efficient cancer gene therapy with a Del1 fragment administered by hypodermic injection in a mouse explanted tumor model - Kitano, Hisataka; Ishikawa, Tomomi; Tamura, Eri; Kokubun, Shinichiro; Hidai, Chiaki (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: Cancer gene therapy using non-viral vectors has potential therapeutic value because it can be used repeatedly for long periods with safety and low costs. It has been reported that gene therapy with an E3C1 fragment of Del1 in a mouse explanted tumor model shows long-term effects when intratumorally injected in the form of DNA. The present study examined whether this therapy is effective when injected hypodermically. Methods: Mice with explanted tumors of A431 human squamous carcinoma cells were treated with a non-viral plasmid vector encoding E3C1. The plasmid was injected subcutaneously every week. Evaluation of lifespan and histochemical analyses were then performed. Results: After 2 weeks of treatment, tumor volumes of control and treated mice were 4,988±1,477 and 1,443±1,523 mm3, respectively (control vs. E3C1, P